Characterization of river plume dynamics for a better water quality management - Friedland, René; Neumann, Thomas; Piehl, Sarah; Radtke, Hagen; Schernewski, Gerald (Frontiers in Marine Science, 2025)
Excessive riverine nutrient inputs are a main driver of eutrophication in marine waters. Thus, identifying areas most affected by river plumes is a key challenge for effective water quality management. Transitional waters, which are affected by river plumes, but also have open sea characteristics, are usually merged with larger open sea assessment units. This leads to non-representative spatial units, whose unreliable assessment results cannot support the implementation of measures in order to improve the water quality. An example for this mismatch is the Oder (Odra) river plume area in the southern Baltic Sea. Due to the missing separation of the river plume area from the open sea waters, its management is suffering from the too coarse classification. We apply two model-based techniques to study the spatial and temporal variability of the Oder river plume and to follow the distribution of its nutrients and pollutants in the sea. Based on the results, we propose an improved layout for the assessment unit that better captures the spatial heterogeneity. By applying a one-way ANOVA, we show that the best size and shape of the river plume assessment unit depend on the water quality indicator being used. A smaller assessment unit near the river mouth is best for dissolved nutrients, while an area nearly four times larger is better, if chlorophyll-a is assessed. Furthermore, thresholds defining the Good Environmental Status (GES) are derived for the new unit and the remaining offshore area. These thresholds align with natural gradients and are consistent with existing GES targets already adopted by the member states of the Baltic Marine Environment Protection Commission.